Cooperating with external partners: the importance of diversity for innovation performance. (1st January 2014) - Beck, Mathias; Schenker-Wicki, Andrea
This paper investigates how diversity in R&D cooperation networks affects firms' innovation performance output as measured by each firm's sales share of innovative products. To address this question, the authors analyse a large-scale sample of micro-data on Swiss firms from five waves (1999, 2002, 2005, 2008 and 2011) of the Swiss innovation survey using panel data analysis. The findings suggest that firms with greater diversity in their cooperation network benefit by generating new product innovations and that the diversity benefit is greatest for small firms. The study further detects a curvilinear relationship between diversity of collaborator types and innovation performance, and emphasises the importance of appropriate HRM and knowledge management policies and practices in providing firms with an effective mechanism for maximising the benefits from diversified cooperation networks.